Representasi Budaya Sehat dalam Cerita Pendek “Nemuri Usagi” Karya Hoshi Shinichi - Priventa, Hendrike; Darmawan, Ricky; Santoso, teguh; Hakim, Difa Aufar; Firmansyah, Renovan Zeta (IZUMI, 2026)
This study explores the representation of healthy culture in Hoshi Shinichi’s short story “Nemuri Usagi” (The Sleeping Rabbit), focusing on how the narrative reflects Japanese values related to physical, mental, and social well-being. Using a qualitative descriptive approach and literary anthropology framework, the analysis identifies cultural elements that construct a holistic concept of health in Japanese society. The findings reveal that “Nemuri Usagi” portrays health not merely as the absence of illness, but as an integration of discipline, harmony, and mindfulness in daily life. Through symbolic characters and minimalist storytelling, Hoshi Shinichi emphasizes the balance between rest and productivity, individual awareness and collective responsibility. This study highlights how modern Japanese literature can serve as a medium for promoting cultural perspectives on health that combine tradition, ethics, and humanism.   gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor